Hypertension with primary aldosteronism is associated with increased carotid intima‐media thickness and endothelial dysfunction. Issue 7 (12th June 2019) - Demirkiran, Ahmet; Everaars, Henk; Elitok, Ali; van de Ven, Peter M.; Smulders, Yvo M.; Dreijerink, Koen M.; Tanakol, Refik; Ozcan, Mustafa
Abstract: Patients with primary aldosteronism induced hypertension are more likely to experience cardiovascular events compared to patients with essential hypertension. Primary aldosteronism may therefore have distinct adverse effects on cardiovascular structure and function, independent of hypertension. However, current data on such effects of primary aldosteronism are conflicting. The aim of the present study was to investigate the influence of primary aldosteronism on vascular structure and endothelial function, using intima‐media thickness as a vascular remodeling index and flow‐mediated dilation as a functional parameter. In total, 70 participants were recruited from patients with resistant hypertension. Twenty‐nine patients diagnosed with primary aldosteronism and 41 patients with essential hypertension were prospectively enrolled. Primary aldosteronism was due to aldosterone‐producing adenoma in 10 cases and due to idiopathic adrenal hyperplasia in 19 cases. All patients underwent ultrasound of the common carotid intima‐media thickness and flow‐mediated dilation of the brachial artery. Primary aldosteronism patients had significantly lower flow‐mediated dilation (3.3 [2.4‐7.4] % vs 14.7 [10.3‐19.9] %, P < 0.01) and significantly higher carotid intima‐media thickness (0.9 [0.7‐1.0] mm vs 0.8 [0.6‐0.9] mm, P = 0.02) compared to patients with essential hypertension. These differences remained significant after adjusting for age, sex, diabetes mellitus, 24‐hours systolic blood pressure, and smoking ( P < 0.01). No differences in either outcome were observed between the adenoma and adrenal hyperplasia groups (both P > 0.05). Hypertensive patients with hyperaldosteronism appear to exhibit deteriorative effects on both vascular structure and function, independent of hypertension.